(3TQM CQLhRI HbQGWs - (3CMeO Hf YHOGYRjR Hf eMeO GHf GdYLej GdTGaYjs; (3GdMcje HbQGWs
(3ChdgG (B:s
(3hHYO agPG JMUjd eG bOQ JMUjdg ef TQM CQLhRI HbQGW , LGeYkG ddHjGf hGdEjLGR bGd HbQGW (B: (3Ef GdOhGA gh GdMei YfO GdSbe hGdOGA jHOh ef WQjbI GdJNe s
(3BNQgG (B:s
(3Ke jLPHGf ghGA LOjOkG gcPG OGFHjf aJHGQc Gddg CMSf GdNGdbjf JeJ GdCQLhRI HTQMgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3bdjdI GdfbWs
(3hGdfSNI ebGHdI hHgG JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdWHs